HUBUNGAN FAKTOR IBU, POLA PEMBERIAN MAKANAN DAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA 12-59 BULAN DI KELURAHAN BATARAGURU - WANTI AYU GUSTRIANI; Waode Azfari Azis; Taswin Taswin (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2023)
National Basic Health Research in Indonesia showed stunting increased from 36.8% to 37.2%. The purpose of this study was to find out the relationship between maternal factors, exclusive feeding and breastfeeding patterns with stunting events in toddlers aged 12-59 months in the working area of the Bataraguru Village Health Center. The type of research used is quantitative research with a case control approach. The population in this study was 621 toddlers. The subjects in the study were all selected cases and controls with a case ratio and 1:1 control. Data processing is carried out using the SPSS . The data analysis in this study is univariate and bivariate, using the Chi-Square Test statistical test by reviewing the p-value test if < alpha (a=0.05) is said to be related. Stastistic test results found that variables unrelated to stunting events were maternal factor (p = 0.032 < 0.05), feeding patterns (p = 0.361 > 0.05), Exclusive breast milk (p = 0.309 > 0.05). The conclusion of this study is that there is a relationship between maternal factors and the incidence of stunting in toddlers 12-59 months in Bataraguru Village. There is no relationship between the pattern of exclusive feeding and breastfeeding and the incidence of stunting in toddlers 12-59 months in Bataraguru Village. The advice from researchers is that it is hoped that mothers of toddlers can prepare themselves during pregnancy by increasing knowledge so as to reduce the risk of stunting in toddlers.